Pengaruh Penambahan Karbon Aktif Fly Ash Batubara Terhadap Emisi Karbondioksida di Top Soil Tanah Mineral - sasmita, aryo; Andrio, David; Aurelia, Keyla (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
Soil respiration is the main pathway for the transfer of carbon dioxide (CO2) emissions from ecosystems to the atmosphere, making it a major contributor to CO2 emissions from the agricultural sector. The use of activated carbon can improve the physical, chemical, and biological properties of the soil, making it a potential useful material for reducing CO2 emissions resulting from the soil respiration process. The purpose of this study was to determine the effect of adding activated carbon from coal fly ash in reducing CO2 emissions in mineral topsoil. Activated carbon was filtered with a 60-mesh sieve and activated using 30% H3PO4 for 24 hours, then added to the soil at various doses of 0, 8, 10, and 12% with an incubation time of 10 days. The activated carbon from coal fly ash produced met SNI 06-3730-1995 for water content, ash content, volatile matter content, bound carbon content, and iodine value. CO2 emissions from soil respiration rates were measured using the acid-base titration method. The results of the study showed that the addition of activated carbon from coal fly ash could not reduce CO2 emissions from the soil respiration process but instead had an impact on increasing CO2 emissions. The highest CO2 emissions were produced in soil treatment with the addition of a 10% activated carbon dose, namely 0.06144 mgCO2-C/g soil or increasing CO2 emissions by 87% compared to without the addition of an activated carbon. Activated carbon from coal fly ash in this study has met the quality requirements of activated carbon with a water content of 5%, ash content of 7%, volatile matter content of 22%, bound carbon content of 66% and iodine number value of 926.37 mg/g.